1961
DOI: 10.1038/bjc.1961.6
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function in Relation to Mammary Cancer

Abstract: THE direct or indirect influence of certain hormones, e.g. stilboestrol and testosterone, on the aetiology of malignancy has been well recognised for many years and has formed the basis of their extensive use in the management of this disease, particularly in attempting its control in advanced stages. Some of the cancers of breast and of prostate are good examples of tumours which are hormone dependent. But the role that the thyroid hormone plays is still uncertain. Beatson was the first, in 1896, to treat adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1962
1962
1980
1980

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…No significant difference was, however, observed between local and side spread breast cancer. Sicker andWaterhouse (1961 , 1967) have shown that there is no statistical difference in radioiodine uptake between the patients with early and late breast cancer nor relationship of thyroid function to the clinical course of these patients. These studies of thyroid function on the patients with breast cancer have no unequivocal evidence.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was, however, observed between local and side spread breast cancer. Sicker andWaterhouse (1961 , 1967) have shown that there is no statistical difference in radioiodine uptake between the patients with early and late breast cancer nor relationship of thyroid function to the clinical course of these patients. These studies of thyroid function on the patients with breast cancer have no unequivocal evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent papers have investigated a possible relationship between the incidence of breast cancer and decreased activity of the thyroid gland (Loeser, 1954;Sommers, 1955;Ellerker, 1956;Rawson, 1956;Edelstyn, Lyons and Welbourn, 1958;Marques, Bru and Espinosse, 1959;Hortling, Hilsi-Brummer and Bjorresten, 1959;Finley and Bogardus, 1960;Carter and Feldman, 1960;Reeve et al, 1961 ;Sicher and Waterhouse, 1961). The relationship has been investigated by demographic, biochemical and experimental approaches.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the literature in our paper of 1961, and described the early stages of an experimental approach we were making in an attempt to answer the question (Sicher and Waterhouse, 1961 More than one type of relationship between thyroid function and breast cancer has been considered in the recent literature, and it is not always clear what is under investigation in a particular study. The hypothesis that hyperfunction of the thyroid gland is associated with a reduced incidence of breast cancer is supported by Humphrey and Swerdlow (1964) who found no case of breast cancer among 196 patients with hyperthyroidism followed for 12 years.…”
mentioning
confidence: 99%